2012
DOI: 10.3126/njst.v12i0.6518
|View full text |Cite
|
Sign up to set email alerts
|

Study on Antibacterial Activity of Common Spices

Abstract: Spices have been shown to possess medicinal value, in particular, antimicrobial activity. They are used as household medicines as well as preservatives of food materials. This study compares the sensitivity of some human pathogenic bacteria to various spice extracts viz. essential oils, acetone and methanol extracts by agar well diffusion method. Of the different spices tested clove, ajowan and cinnamon were found to possess relatively higher antimicrobial activities. Essential oil of cinnamon showed broad spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…both gram positive and gram negative). The broad spectrum antibacterial activity of garlic and green tea is also reported previously by many researchers [36][37][38][39]. Similar to our findings, Farjana et al [40] reported antibacterial activity of green tea against S. aureus, but no activity against E. coli.…”
Section: Preliminary Study Of Methanol and Water Extracts Of Plant Products On Lab Culturessupporting
confidence: 92%
“…both gram positive and gram negative). The broad spectrum antibacterial activity of garlic and green tea is also reported previously by many researchers [36][37][38][39]. Similar to our findings, Farjana et al [40] reported antibacterial activity of green tea against S. aureus, but no activity against E. coli.…”
Section: Preliminary Study Of Methanol and Water Extracts Of Plant Products On Lab Culturessupporting
confidence: 92%
“…Syzygium aromaticum has shown maximum zone of inhibition at 50mg/mL concentration against Staphylococcus aureus ( 23 has reported MBC value (20mg/mL) of clove against E. coli whereas another study done by Mahajan et al 24 has shown MBC against Staphylococcus aureus and Pseudomonas aeruginosa ranging between 6.25 -25mg/ml, which is slightly higher to our study in which MBC came out to be 6.25 mg/mL against all biofilm producing MDR isolates. In the present study, biofilm reduction was more than 50% at each concentration of clove extracts (50, 25, 12.5, 6.25 mg/mL).…”
Section: Discussioncontrasting
confidence: 75%
“…Several researchers have investigated the individual effects of essential oils of spices and medicinal plants on antimicrobial activity against food borne bacteria as well as antioxidant activity. Study performed by Maharjan et al (2012) compares the sensitivity of some human pathogenic bacteria to various spice extract viz. essentials oils, acetone and methanol extracts by agar well diffusion method.…”
Section: Date Of Submission: October 2 2019mentioning
confidence: 99%